2021
DOI: 10.1038/s41598-021-96022-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-related psychological distress fully mediates the association from social impact to sleep disturbance among patients with chronic schizophrenia

Abstract: The aims of the current study were to identify factors associated with sleep disturbance and Coronavirus disease-19 related psychological distress (CPD), and to develop a conceptual model to verify the mediating effect of CPD on the association between social impact and sleep disturbance. This study recruited patients with schizophrenia. Factors associated with the level of sleep disturbance and CPD were identified using univariate linear regression, and further selected into a stepwise multivariate linear reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…This is our second-year follow up study by our group, and the first year outcome has been published elsewhere [ 4 , 52 , 53 , 54 ]. We recruited participants through printed advertisements posted in the public area in the Kaohsiung Municipal Kai-Syuan Psychiatric Hospital in Taiwan, from 30 May 2021 to 30 June 2021.…”
Section: Methodsmentioning
confidence: 99%
“…This is our second-year follow up study by our group, and the first year outcome has been published elsewhere [ 4 , 52 , 53 , 54 ]. We recruited participants through printed advertisements posted in the public area in the Kaohsiung Municipal Kai-Syuan Psychiatric Hospital in Taiwan, from 30 May 2021 to 30 June 2021.…”
Section: Methodsmentioning
confidence: 99%
“…Among the psychological consequences of the pandemic and the lockdowns, the patients reported increased anxiety, depression, and health risky behaviors [35,36]. A Taiwanese study has shown that COVID-related psychological distress fully mediated the association from social impact to sleep disturbance among patients with chronic schizophrenia [37]. A qualitative Turkish study concluded that most of the patients with schizophrenia shared the same challenges with the general population coping with the pandemic, with sometimes different coping strategies [38].…”
Section: Key Pointsmentioning
confidence: 99%
“…In Taiwan, people also suffer from massively psychological distress during COVID-19 pandemic. Several studies based on either the general public [9] or patients with mental disorders [10,11] in Taiwan have also reported undesirable psychological impacts during the COVID-19 pandemic, including sleep disturbance,…”
Section: Psychological Impact Of the Covid-19 Pandemicmentioning
confidence: 99%
“…In Taiwan, people also suffer from massively psychological distress during COVID-19 pandemic. Several studies based on either the general public [ 9 ] or patients with mental disorders [ 10 , 11 ] in Taiwan have also reported undesirable psychological impacts during the COVID-19 pandemic, including sleep disturbance, depression, and even suicidal ideation. Furthermore, COVID-19 pandemic is also associated with predominantly psychological burden among elderly, [ 12 14 ] patients with mental illness, [ 15 ] and students.…”
Section: Introductionmentioning
confidence: 99%